Identification of the thickness and depth of coal seams using the Schlumberger configuration geoelectric method in Petai Village, Singingi Hilir District, Kuantan Singingi Regency - Sherly Mutiara; Usman Malik; Juandi Muhammad; Hijrah Septia Anisa (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2024)
The identification of the thickness and coal seam depth using the Schlumberger configuration geoelectric method in Petai Village, Singingi Hilir District, Kuantan Singingi Regency, Riau Province has been investigated. This study aims to determine the subsurface structure and its depth. The method used in this study is the one-dimensional Schlumberger configuration geoelectric method by processing data using Progress software. The data obtained are (I) and potential difference (V). Based on the results of data processing, the information on rock layers at the research site is obtained. The resistivity value of rocks on track 1 ranger from 2,272.23 – 1,317.96 Ohm-m with a depth of up to 19.05 meters. The lithology layers identified the resistivity values obtained for track 1 are sand and dry gravel. The resistivity value of the second trajectory range 1,188.91 – 1,491.29 Ohm-m with a depth of up to 17.00 meters. The lithology layers identified the resistivity values obtained for track 2 are top soil, coal and sandstone. The resistivity value of the third trajectory range 4,986.17 – 347.81 Ohm-m with a depth of up to 11.43 meters. The lithology layers identified the resistivity values obtained for track 3 include sandstone, coal and sand. The result of the interpretation of track 1, track 2 and track 3 obtained the subsurface layers and its depth at the research location.